Climatology and trends of the Euro‐Mediterranean thermal bioclimate. (30th March 2018) - Giannaros, Theodore M.; Kotroni, Vassiliki; Lagouvardos, Konstantinos; Matzarakis, Andreas
Abstract : High‐resolution numerical simulations were carried out for the most recent 30‐year period (1987–2016), focusing on the Euro‐Mediterranean region. A sophisticated thermo‐physiologically significant thermal index, namely the physiologically equivalent temperature (PET), was computed for assessing the thermal bioclimate of the study area and for investigating the presence of long‐term trends, focusing on bioclimatic extremes. Results indicate that the Euro‐Mediterranean thermal bioclimate follows a zonal pattern, upon which topography acts to delineate regional maxima and minima. The conducted time series analysis reveals statistically significant trends that are generally more pronounced for cold extremes. In particular, it is found that the number of days with cold (hot) stress has decreased (increased), with the distribution of PET exhibiting warming of both its cold and warm tail. The south–east Mediterranean and the Balkans are found to be the most responsive to bioclimatic changes, showing coherent and statistically significant warming trends. Overall, the results of this study provide a new point of view of the Euro‐Mediterranean climate, which could be of usefulness in a wide range of future applications. The detailed spatio‐temporal bioclimatic data could be exploited, for instance, to support applications related to tourism and recreation, highlighting regions with favourable or less favourable thermal comfort conditions. Furthermore, the trend data could be employed for quantifying the vulnerability of certain regions to cold and heat stress, in the context of public health applications. Abstract : A high‐resolution thermal bioclimate atlas is presented for the Euro‐Mediterranean region, which could be exploited in the context of tourism and recreation applications, as well as for highlighting regions that are vulnerable to hot and cold stress. Overall, the presented results provide evidence that the Euro‐Mediterranean thermal bioclimate has become warmer over the past 30 years, particularly in the eastern part of the study area.